Extragalactic optical and near-infrared foregrounds to 21-cm epoch of reionisation experiments. Issue Volume 12:Issue S333(2017) (8th May 2018) - Jarvis, Matt J.; Bowler, Rebecca A.A.; Hatfield, Peter W.
Abstract: Foreground contamination is one of the most important limiting factors in detecting the neutral hydrogen in the epoch of reionisation. These foregrounds can be roughly split into galactic and extragalactic foregrounds. In these proceedings we highlight information that can be gleaned from multi-wavelength extragalactic surveys in order to overcome this issue. We discuss how clustering information from the lower-redshift, foreground galaxies, can be used as additional information in accounting for the noise associated with the foregrounds. We then go on to highlight the expected contribution of future optical and near-infrared surveys for detecting the galaxies responsible for ionising the Universe. We suggest that these galaxies can also be used to reduce the systematics in the 21-cm epoch of reionisation signal through cross-correlations if enough common area is surveyed.